INDEX OF PREPONDERANCE—A METHOD OF GRADING THE FOOD ELEMENTS IN THE STOMACH ANALYSIS OF FISHES - Natarajan, A V; Jhingran, A G (Indian Journal of Fisheries, 2011)
VARIOUS methods are in prevalence in the studies of stomach analysis offishes and these were critically discussed by Hynes (1950) and Pillay (1952).They comprise chiefly in studying the frequency of occurrence of food itemsas well as bulk. The ’occurrence’ method is insulated from the quantitativeelement and similarly quantitative methods of ’occurrence’ element.On account of the restricted scope of these two types of analyses they areindividually not suited for the purpose of grading the food components ofgut contents. An Index taking these two factors into consideration seemsto be desirable for this purpose and accordingly a composite Indexâ€”designatedas the ’Index of Preponderance’â€”was constructed from volume and’occurrence’ index. The mean Index of feeding, proposed by lizuka et af.(1954) is different in scope and considers the ratio of volume of the feed tovolume of animal, the volume being treated as a function of length. Theirmethod gives an index of feeding intensity.